Almost Periodic Solutions for Second Order Dynamic Equations on Time Scales - Yan Wang; Lan Li (Discrete Dynamics in Nature and Society)
We firstly introduce the concept and the properties of Cm almost periodic functions on time scales, which generalizes the concept of almost periodic functions on time scales and the concept of C(n)-almost periodic functions. Secondly, we consider the existence and uniqueness of almost periodic solutions for second order dynamic equations on time scales by Schauder’s fixed point theorem and contracting mapping principle. At last, we obtain alternative theorems for second order dynamic equations on time scales.